Measles vaccination: Threat from related veterinary viruses and need for continued vaccination post measles eradication - Sara Louise Cosby; Leanne Weir (Taylor & Francis Group, 2018)
Measles virus (MV) is the only human virus within the morbillivirus genus of the Paramyxoviridae. The veterinary members are canine distemper virus (CDV), peste des petits ruminants virus (PPRV), Rinderpest Virus (RPV) as well as the marine morbilliviruses phocine distemper virus (PDV), dolphin morbillivirus (DMV) and porpoise morbillivirus (PMV). Morbilliviruses have a severe impact on humans and animal species. They confer diseases which have contributed to morbidity and mortality of the population on a global scale. There is substantial evidence from both natural and experimental infections that morbilliviruses can readily cross species barriers. Of most concern with regard to zoonosis is the more recently reported fatal infection of primates in Japan and China with strains of CDV which have adapted to this host. The close genetic relationship, shared cell entry receptors and similar pathogenesis between the morbilliviruses highlights the potential consequences of complete withdrawal of MV vaccination after eradication. Therefore, it would be prudent to continue the current MV vaccination. Ultimately development of novel, safe vaccines which have higher efficacy against the veterinary morbilliviruses is a priority. These would to protect the human population long term against the threat of zoonosis by these veterinary viruses.